PENGARUH PENGEMBANGAN KARIR TERHADAP TURNOVER INTENTION MELALUI KINERJA KARYAWAN YANG DIMODERASI OLEH BUDAYA ORGANISASI - Netty Situmorang; Abdul Haeba Ramli; Heru Kreshna Reza (JURNAL LENTERA BISNIS, 2023)
Intention to move is an early indicator of someone's possibility of leaving their job. The tendency for employees to leave can lead to a number of negative impacts including company costs to recruit and train new employees, lower productivity, volatility in terms of overall company performance and reduced satisfaction among remaining employees. The purpose of this study is to determine the effect of career development on turnover intention through employee performance which is moderated by organizational culture. Research data was collected using a questionnaire distributed during the survey period in July 2023 to 200 employees. Research data was processed and analyzed using the Structural Equation Model Partial Least Square (SEM-PLS). The results of the study show that career development has no significant effect on turnover intention, in other words the data does not support the hypothesis. Organizational culture does not moderate the relationship between career development and employee performance, in other words the data does not support the hypothesis. Key words: Career Development, Turnover Intention, Employee Performance, Organizational Culture